Physiological characterization of sugarcane's endophytic microbial community - Anar Janet Rodríguez Cheang; Iván David Trujillo Cerón; Yaremis Felipe Bringas (Revista Colombiana de Biotecnología, 2007)
Excessive application of chemical nitrogen fertilisers and pesticides has badly affected the environment. This has led to great interest being shown in studying a crop's native microbial community and its benefit for plants. This paper was thus aimed at characterising sugarcane's endophytic microbial community. 5 sugar cane strains and 50 isolates were used. Gas chromatography was used for measuring nitrogenase activity and the influence of carbon and nitrogen sources and pH on cultures. Indol acetic (IAA) production was detected by Dot-Immunobinding and Salkowski's method. These results show that 19 strains and isolates had nitrogenase activity, values ranging from 100 to SOOO/zg/mL; 6 of them produced IAA (values ranging from 1,7 to 2,5 //g/mL): Gluconacetobacter diazotrophicus PAl-5, Gluconacetobacter diazotrophicus 1-05, Gluconacetobacter diazotrophicus 4-02,17,30 and 305. It was demonstrated that culture medium nutrient sources and pH affected the nitrogenase activity of the strains representing the endophytic community.